Non-Suicidal Self-Injury and Perfectionism - Tonta, Kate Elizabeth (Curtin University, 2022)
Kate’s PhD investigated the association between perfectionism and non-suicidal self-injury. Integrating the existing knowledge about perfectionism and non-suicidal self-injury, Kate proposed potential mechanisms to understand this relationship, incorporating the role of attentional processes, rumination, and negative emotion. This PhD included a range of research methods, including self-report and behavioural measures. The findings of this research provide new insights into the relationship between perfectionism and non-suicidal self-injury, and have clinical and theoretical implications for this field.